(untitled) (Repertorio Científico, 2020)
It was evaluated the effect of industrial residue on the Deli x Ghana variety in a commercial plantation. Different increasing doses (5000 kg ha-1, 10 000 kg ha-1 and 15 000 kg ha-1) was applied. This was located at the palm slices in a randomized complete block design. Nutrient soil concentration, root density and stomatic conductance were evaluated at 90 and 180 days after their application (dda). It was found that after 180 dda that pH increased and decreasing soil acidity. Root density also increased at 90 dda with the addition of 10 000 kg ha-1 (C10) and at 180 dda with the application of 5000 kg ha-1 and 15 000 kg ha-1 (C5 and C15). Stomatic conductance showed significant statistical difference in treatments C5, C10 and C15 on sheet N ° 9 at noon. It was concluded addition of industrial oil palm ash had a positive effect on the variation of stomatic conductance in oil palm and root density.